Radical Interventions: Ed Herman's Intellectual Roots and Activism within the Political Economic Tradition - Victor Pickard; Todd Wolfson (Media Theory, 2018)
This essay reflects on Ed Herman's legacy by connecting his intellectual background to the anti-fascist project within the political economic tradition of communication research. Given that one of the authors (Todd Wolfson) was good friends with Ed and worked with him on independent media, we also consider how he applied his radical critique to local activist projects in Philadelphia. This analysis helps underscore the fact that Ed Herman's insights hold much contemporary relevance for the many political problems facing American and global society today.